Complete small colon ablation and fixation of the mesocolon to the internal anal sphincter due to prolapse in a young draft horse - Cristian Mihăiță Crecan; Valeria Ciulu-Angelescu; Alexandru-Florin Lupșan; Denisa Bungărdean; Zsofia Daradics; Mirela Alexandra Tripon; Iancu Adrian Morar; Cosmin Petru Peștean (Cluj Veterinary Journal, 2023)
A two-year-old draft stallion was referred for evaluation of a type IV prolapse. A thorough physical examination followed by blood tests was performed to assess the situation. Following the examination, it was concluded that the protruded small colon was devitalised, measured approximately one and a half meters and mesenteric and vascular injury were present. A standing surgery approach was chosen for the present case, in which the affected tissue was excised and the remaining mesentery was ligated to the internal anal sphincter to decrease pressure during straining in the physiological act of defecation. Six months later, after an uneventful recovery, the stallion was in good health and performing its reproductive duties. To our knowledge, this is the first report of a mesenteric fixation to the internal anal sphincter in a horse. The study confirms that this technique is a feasible method that can be used in the complete ablation of the small colon in prolapses.